A facile way to optimize photoelectric properties of SnSe nanosheets via sonication assisted liquid-phase exfoliation - Duong, Thiet Van; Nguyen, Dung Dinh; Nguyen, Hong Tuan; Pham, Nhat Van; Chung, Nguyen Xuan; Luong, Bac Huu; Phan, Hong Ngoc (Vietnam Journal of Science and Technology, 2022)
Layer-structured SnSe is known as a potential semiconductive material because it is not toxic, relatively abundant in the earth crust and possess unique electronic, optoelectronic properties. This material is also broadly used for many applications such as photodetector, fire detector, thermoelectric devices, energy storing equipment, etc. Its properties can be tuned by changing fabrication methods. In this work, we report on the process of fabricating SnSe nanosheets (SnSe NSs) in a thin film by using a sonication-assisted exfoliation method and a transferring process of SnSe NSs to a SiO2/Si substrate for photoelectric characterization. The properties of fabricated thin film was characterized by X-ray diffraction, Raman spectroscopy, Atomic Force Microscopy, Scanning Electric Sspectroscopy and photoelectrical conduction measurement. The obtained results show the optimal exfoliation conditions with a duration of 24 hours and an SnSe NS thickness of 2.5 nm. The highest photoresponsivity isapproximate 65 mAW−1 and response time is found around 0.95 s for the case of 62.5 µm SnSe film’s thickness. The photocurrent is approximately linear illumination-intensity dependent with an ideal factor of 0.87 under a constant bias of 2.0V and an exciation wavelength of 450 nm. We introduce a simple method of fabrication and controllable photoelectric properties of SnSe NSs.